The Transient Receptor Potential Vanilloid 1 Antagonist Capsazepine Improves the Impaired Lung Mechanics during Endotoxemia. Issue 5 (24th May 2016) - Cabral, Layla D. M.; Giusti‐Paiva, Alexandre
Abstract: Acute lung injury (ALI) caused by systemic inflammatory response remains a leading cause of morbidity and mortality in critically ill patients. Management of patients with sepsis is largely limited to supportive therapies, reflecting an incomplete understanding of the underlying pathophysiology. Furthermore, there have been limited advances in the treatments for ALI. In this study, lung function and a histological analysis were performed to evaluate the impact of transient receptor potential vanilloid‐1 receptor (TRPV1) antagonist (capsazepine; CPZ) on the lipopolysaccharide (LPS)‐induced lung injury in mice. For this, adult mice pre‐treated with CPZ or vehicle received intraperitoneal injections of LPS or saline and 24 hr after, the mice were anaesthetized, and lung mechanics was evaluated. The LPS‐challenged mice exhibited substantial mechanical impairment, characterized by increases in respiratory system resistance, respiratory system elastance, tissue damping and tissue elastance. The pre‐treatment with CPZ prevented the increase in respiratory system resistance and decreased the increase in tissue damping during endotoxemia. In addition, mice pre‐treated with CPZ had an attenuated lung injury evidenced by reduction on collapsed area of the lung parenchyma induced by LPS. This suggests that the TRPV1 antagonist capsazepine has a protective effect on lung mechanics in ALI during endotoxemia and that it may be a target for enhanced therapeutic efficacy in ALI.